Polybrominated diphenyl ether (PBDE) neurotoxicity: a systematic review and meta-analysis of animal evidence. (19th May 2018) - Dorman, David C.; Chiu, Weihsueh; Hales, Barbara F.; Hauser, Russ; Johnson, Kamin J.; Mantus, Ellen; Martel, Susan; Robinson, Karen A.; Rooney, Andrew A.; Rudel, Ruthann; Sathyanarayana, Sheela; Schantz, Susan L.; et al.
ABSTRACT: A recent systematic review (SR) and meta-analysis of human studies found an association between prenatal serum polybrominated diphenyl ethers (PBDE) concentrations and a decrease in the IQ of children. A SR of experimental developmental animal PBDE-mediated neurotoxicity studies was performed in the present study. Outcomes assessed included measures related to learning, memory, and attention, which parallel the intelligence-related outcomes evaluated in the human studies SR. PubMed, Embase, and Toxline were searched for relevant experimental non-human mammalian studies. Evaluation of risk of bias (RoB) and overall body of evidence followed guidance developed by the National Toxicology Program. Animal studies using varying designs and outcomes were available for BDEs 47, 99, 153, 203, 206, and 209 and the technical mixture DE-71. Study reporting of methods and results was often incomplete leading to concerns regarding RoB. A meta-analysis of 6 Morris water maze studies showed evidence of a significant increase in last trial latency (effect size of 25.8 [CI, 20.3 to 31.2]) in PBDE-exposed animals with low heterogeneity. For most endpoints, there were unexplained inconsistencies across studies and no consistent evidence of a dose-response relationship. There is a "moderate" level of evidence that exposure to BDEs 47, 99, and 209 affects learning. For other PBDEs and other endpoints, the level of evidence was "low" or "very low". The meta-analysis led to stronger conclusions than that based upon a qualitative review of the evidence. The SR also identified RoB concerns that might be remedied by better study reporting.